Grouping of Ankyloglossia According to Coryllos Anatomical Classification and Follow-Up Results for Breastfeeding: Single-Center, Cross-Sectional Study - Mehmet Ali Narsat; Abdulvehhap Beygirci; Gökçen Tuğçe Özdönmez; Eren Yıldız (MDPI AG, 2022)
Ankyloglossia is a condition of limited tongue mobility caused by a short lingual frenulum. The diagnosis and treatment of ankyloglossia are still controversial. The main clinical problems encountered during breastfeeding are difficulty in sucking and its clinical reflections. This study aims to evaluate the infant population born with ankyloglossia and to determine the results of frenotomy. We conducted an observational, cross-sectional study among infants born in a tertiary hospital. We included all infants born between 1 January and 30 June 2022. The neonatal follow-up protocol for ankyloglossia was determined before the defined dates, and data were recorded during the screening period. The recorded data were retrospectively collected from the files. Within six months, 705 infants were born. Due to additional problems and other conditions that prevent breastfeeding, evaluable data of 207 (29.3%) infants could not be provided. Of the remaining 498 infants, 234 (33.2%) had ankyloglossia. While none of the infants without ankyloglossia had a breastfeeding problem after appropriate training, 28.6% of the ankyloglossia group had a breastfeeding problem (p < 0.001). The need for frenotomy differed significantly between Coryllos groups (p < 0.001). Breastfeeding was unsuccessful before frenotomy in 12 Coryllos type-1 patients, and all had difficulty in sucking. Frenotomy was performed within the three-month follow-up period in all patients with complaints of inability to firmly grasp the breast, nipple slipping from the mouth, and nipple biting during the first 24 h. In terms of breastfeeding problems, regardless of the anatomical typology, frenotomy can be performed safely in early life with successful results. If deficiencies or difficulties in breastfeeding are noticed in ankyloglossia patients even at the first control, frenotomy should be recommended in clinical conditions.